ANALISIS LAPORAN KEUANGAN DALAM MENILAI KINERJA KEUANGAN PERUSAHAAN PADA BANK PERKREDITAN RAKYAT (BPR) DANA RAYA MANADO - Rabuisa, Wilna Feronika; Runtu, Treesje; Wokas, Heince R. N. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
In the world of banking, finance is very influential on the continuity of the activities of a banking as well as any individual in the banking it. In a company also required an analysis of financial statements to determine the companys ability to overcome the companys financial problems as well as decision making fast and precise. The formulation of the problem in this research is how the financial performance of Rural Banks (BPR) Dana Raya Manado period 2014-2016. The purpose of research is to know the financial performance of Rural Banks (BPR) Dana Raya Manado period 2014-2016. Data analysis technique used in this study by using bank financial ratios. Based on the results of research on the financial ratios of corporate banks are still experiencing fluctuations. Assessment of the Liquidity of Rural Banks Manado Funds Fund is still able to pay its financial obligations. Assessment of Solvency The Bank has adequate capital. Assessment of the companys profitability still has an increased profit.Keywords : Financial Statement, Financial Ratios, Profitabilitas, Rentabilitas